The use of the internet to attract tourists to Zimbabwe: an analysis of the Zimbabwe Tourism Authority website - Govere, W.D. Tsokota, Theo. Chikuta, O. Mukwembi, A. Chinofunga, P. (Cosmic Journals, 2014)
The continuing rise of the internet as a communications tool for organizations in this informational era presents greater opportunities for marketing activities for tourism enterprises. In other words, the internet serves as a new communication and distribution channel for relevant and necessary tourism information. It is therefore Zimbabwe Tourism Authority’s’ mandate to lure tourists to Zimbabwe using this communication and distribution channel. Zimbabwe Tourism Authority (ZTA) has since employed various marketing techniques to try and lure back the tourists. Among the different and most interesting strategies being used by ZTA, a sound web presence in the form of a good and informative website. This paper looks at the potentials inherent in internet technology and highlights how it can be useful in promoting tourism. The research will give Zimbabwe Government, Zimbabwe Tourism Authority (ZTA) and other Organizations involved in promoting Zimbabwe insight on the current situation regarding tourism and the internet in Zimbabwe. To achieve this we assessed the ZTA webpage to determine whether it gives adequate and relevant information to attract tourists.